Space between concern and crime - Silver, James (Criminology & public policy, 2020)
Amid widespread agreement that public mass violence is generally the result of understandable and often discoverable thoughts and behaviors, the threat assessment model of identifying, assessing, and managing potential offenders has proven an effective safety approach across different offender types. In this article I describe two impediments to the model's efficacy - incomplete national adoption of the model, and the disinclination of some bystanders to report concerning behaviors potentially related to public mass violence. I propose addressing the first of these obstacles by encouraging use of dissemination and implementation science, and the second by extending emerging application of social norms concepts. Each approach leverages the strength of existing (and developing) threat assessment strategies and highlights potentially productive areas for research and policy innovation.